2003
DOI: 10.1074/jbc.m210712200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation or Glutamic Acid Substitution at Protein Kinase C Sites on Cardiac Troponin I Differentially Depress Myofilament Tension and Shortening Velocity

Abstract: There is evidence that multi-site phosphorylation of cardiac troponin I (cTnI) by protein kinase C is important in both long-and short-term regulation of cardiac function. To determine the specific functional effects of these phosphorylation sites (Ser-43, Ser-45, and Thr-144), we measured tension and sliding speed of thin filaments in reconstituted preparations in which endogenous cTnI was replaced with cTnI phosphorylated by protein kinase C-⑀ or mutated to cTnI-S43E/S45E/T144E, cTnI-S43E/S45E, or cTnI-T144E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
187
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 142 publications
(211 citation statements)
references
References 50 publications
(63 reference statements)
22
187
2
Order By: Relevance
“…Sites at Ser-42, and Ser-44 are substrates mainly for protein kinase C, and when phosphorylated induce a depression in maximum tension, and a decrease in cross-bridge kinetics [24][25][26], as reflected in a depression of thin filament sliding in the motility assay and ATPase rate. On the other hand, it is apparent that phosphorylation of Thr-143 induces an increase in sensitivity to Ca 2+ [27] and an apparent depression in cross-bridge kinetics [25]. As reviewed elsewhere, phosphorylation of sites at Ser-42, Ser-44, and Thr-143 may be considered maladaptive, when and if they predominate as may occur in disorders of the heart [28].…”
Section: Specific Modifications In Troponin I Affect the Dynamics Andmentioning
confidence: 99%
“…Sites at Ser-42, and Ser-44 are substrates mainly for protein kinase C, and when phosphorylated induce a depression in maximum tension, and a decrease in cross-bridge kinetics [24][25][26], as reflected in a depression of thin filament sliding in the motility assay and ATPase rate. On the other hand, it is apparent that phosphorylation of Thr-143 induces an increase in sensitivity to Ca 2+ [27] and an apparent depression in cross-bridge kinetics [25]. As reviewed elsewhere, phosphorylation of sites at Ser-42, Ser-44, and Thr-143 may be considered maladaptive, when and if they predominate as may occur in disorders of the heart [28].…”
Section: Specific Modifications In Troponin I Affect the Dynamics Andmentioning
confidence: 99%
“…In one study, muscles from transgenic mice showed a 45% reduction in maximal force, while the fiber bundles of the transgenic mice in a different study showed a 13% decrease in maximum tension and a 20% increase in maximum MgATP activity compared to fibers from wild-type mice Montgomery et al 2002). Burkart et al (2003) studied phosphorylated cTnI at sites Ser43 and 45 using charge mutations in skinned fibers from mice and in vitro motility assays. Their results showed that charge change at these PKC sites inhibits the actin-myosin interaction by causing decreases in maximum tension, Ca 2+ -sensitivity, and thin filament sliding speed.…”
Section: Thin Filament Regulationmentioning
confidence: 99%
“…Also, a reduction in myofilament length-dependent activation has been observed in cardiac rat trabeculae expressing slow skeletal troponin (ssTn), which has a proline at position 122 versus a threonine at position 143 in cTnI (Table 1) (Tachampa et al 2007). Pseudophosphorylation of Thr143 has been shown to desensitize the filaments to Ca 2+ in an in vitro motility assay (Burkart et al 2003), while phosphorylation of Thr143 by PKCβII in permeabilized cadiac myocytes from mouse in which the PKA sites Ser23/24 were replaced with alanines to avoid cross-phosphorylation showed an increase in the Ca 2+ -sensitivity of tension. Replacement of Thr143 with alanine abolished the response to PKC-βII treatment.…”
Section: Thin Filament Regulationmentioning
confidence: 99%
“…The functional consequence of phosphorylation of this residue has not been fully resolved. On one hand, Burkart et al found that by replacing Thr-144 by Glu to mimic phosphorylation, detergent-skinned cardiac fiber bundles containing mutant cTnI showed no significant difference in Ca 2+ sensitivity and maximum force from those containing wild-type cTnI, whereas in the in vitro motility assay, cTnI with a Thr144Glu mutation displayed desensitization to Ca 2+ [11]. On the other hand, Wang et al showed that when cardiac myocytes expressing cTnI (Ser23Ala/Ser24Ala) were exposed to PKC-bII, phosphorylation of PKCspecific sites induced increased myofilament Ca 2+ sensitization [81].…”
Section: Troponin Imentioning
confidence: 99%
“…Despite the recent finding that these sites are poor substrates for PKC, phosphorylation of these sites has a strong impact on myofilament activity, in particular Ser-45 [72]. For example, substitution of Ser-43/Ser-45 with the charged residue Glu induces a marked depression of actin-activated S1 ATPase activity in solution and a reduction in myofilament Ca 2+ sensitivity [11,48]. This depression of myofilament activity by phosphorylation at these PKC-specific sites appears to be due to stabilization of the thin filament in the off-state [45].…”
Section: Troponin Imentioning
confidence: 99%